A model of the optimal allocation of government expenditures. (19th November 2019) - Fan, Simon; Pang, Yu; Pestieau, Pierre
Abstract: Government expenditures can be used for various socioeconomic objectives, including public education, consumption of public goods and services, and social protection. This paper analyzes the optimal allocation of public expenditures among these competing functions. We establish an overlapping generations model with heterogeneous individuals in which the government optimally chooses income tax, transfer payment, educational spending, and public consumption. Our model characterizes the transitional dynamics and the steady state of each function with and without a pay‐as‐you‐go intergenerational contract. We also conduct a simulation illustrating that the presence of an intergenerational contract may raise public consumption and social welfare in the steady state.